ISOLATION, SCREENING AND IDENTIFICATION OF CEFDINIR DEGRADING YEASTS FOR THE TREATMENT OF PHARMACEUTICAL WASTEWATER - A., SELVI; Das, Nilanjana (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of the present study was to isolate, screen and identify the cefdinir degrading yeasts for the treatment of pharmaceutical wastewater. Methods: The steps include isolation of yeasts from pharmaceutical wastewater, screening of yeasts for cefdinir degradation, studies on effects of pH, carbon and nitrogen sources on yeast growth, treatment of pharmaceutical wastewater using yeast. Results: Out of five yeast isolates, four were screened for cefdinir degradation and identified by molecular techniques. Yeast isolates were found to utilize cefdinir as sole carbon and energy source at an optimum pH 6.0. Addition of extra carbon and nitrogen sources in the growth medium did not show any improvement of yeast growth. Maximum cefdinir degradation by four yeast isolates was found to be 72%, 78%, 81% and 84% respectively and significant reduction in BOD, COD, TSS and TDS was noted after treating the pharmaceutical wastewater with the yeast isolates. Conclusion: The isolated yeasts may serve as potential remediation agents for the treatment of pharmaceutical wastewater containing cefdinir, a semi-synthetic cephalosporin derivative.